Tutoring and Education: Identifying the Opportunities and Challenges of ChatGPT Among Students - Atiyah, Almalky Nabil (Communications in Mathematics and Applications, 2023)
In recent years, a significant number of enhancements are observed in the field of artificial intelligence. ChatGPT is one of the growing technologies which are trained to provide a better understanding of several aspects. ChatGPT can assist the learners with their projects, homework and detailed briefing about different topics with an interactive learning experience. This systematic literature review aims to identify the opportunities and challenges of ChatGPT among students specifically for tutoring and education. As part of systematic literature review, the study accesses various research databases and filters them to identify the opportunities and challenges of ChatGPT among students. The study provides a comparison of current literature to examine the existing limitations and suggests the countermeasures to overcome the identified challenges. The findings of the study provides a detailed explanation of the potential benefits and the limitation of implementing the ChatGPT in the educational environment, in addition to this significant insight into its most effective use for students via an in-depth examination of current literature. Finally, the goal of this systematic review is to add to an extensive understanding basis that can educate teachers, researchers, and administrators on the successful use of ChatGPT in tutoring and education, enabling enhanced learning experiences for students in the digital era. Despite these valuable insights, the study has an impediment that the study completely relies on the systematic literature review which gives a scope for the future researchers to accomplish a quantitative study by using a real time database.